Synthesis of Fluorescent Boron Difluoride Complexes of 3-Acyl-4-hydroxycoumarins - Nyuchev, Alexander V.; Schegravin, Kirill V.; Lopatin, Michail A.; Fokin, Valery V.; Beletskaya, Irina P.; Fedorov, Alexey Yu. (Synthesis, 2014)
A series of boron difluoride–3-acyl-4-hydroxycoumarin complexes were synthesized in good yields in three steps starting from 4-hydroxycoumarins. The boron complexes showed strong luminescence in the green–yellow region and are compatible with surface imaging applications.
Keywords: acylation; carbohydrates; coumarin; click chemistry; fluorescence